Dictionaries for learners of English. (18th March 2016) - Lew, Robert
Abstract : The Department of Lexicography and Lexicology at Adam Mickiewicz University in Poznań has done extensive research on dictionary use in the context of language teaching and learning. The department forms part of the Faculty of English, which is the largest institution in continental Europe educating teachers of English at the B.A., M.A., and Ph.D. levels. Therefore, it is only natural that the language-teaching potential of dictionaries is the main focus of the studies undertaken in the Department.